7 Cardiac CT in a modern chest pain service. (May 2018) - Jackson, Deborah; Morgan-Smith, Dorothy; Jones, Hefin; Machin, Ruth; Watson, Nick; Large, Adrian; Heatlie, Grant; Duckett, Simon
Abstract : Introduction: NICE guidelines were updated in 2016 recommending cardiac CT (CTCA) as first line investigation for suspected stable angina. Meeting these guidelines has been challenging particularly due to varied access to CTCA. At University Hospital North Midlands (UHNM) we adapted our Rapid Assess Chest Pain (RACP) service and increased access to CTCA to become fully NICE compliant. Methods: In November 2017 our RACP clinics became specialist cardiac nurse led. Patients were assessed and investigated in-line with 2016 NICE guidelines. We performed a service evaluation assessing 100 consecutive patient outcomes. Results: Average age 61.5 years (31–84 years), 57 men. 44 patients were considered to have non-cardiac chest pain and discharged. 56 were referred for further investigation, 39 (70%) CTCA, 12 (21%) dobutamine stress echocardiography (DSE) and five (9%) referred for invasive coronary angiography. Outcomes from CTCA (mean age 57.7 years), six (15%) normal and discharged, 21 (55%) minor disease discharged with primary prevention, ten (25%) moderate/severe disease and referred for invasive angiography or functional imaging. Two (5%) patients cancelled investigations. DSE (mean age 74.8 years), six (50%) normal, four (34%) non-diagnostic, one (8%) ischaemic and one (8%) moderate left ventricular dysfunction with regional wall motion abnormality. Invasive coronary angiography, one three vessel disease with severe aortic stenosis, two underwent PCI, one had mild disease and one awaited. Conclusion: Adhering to the 2016 guidelines significantly reduced the number of investigations required. Of the patients referred for CTCA 73% had normal or minor CAD and were discharged with lifestyle advice ±medication.